Health Education Of Children and Adolescents In Implementing Health Protocols During The Covid-19 Pandemic in Bungursari Village - F, Ayunda Alysa; Maruf, Cipta Muhammad; Rizal, Fahrul; Salsabila, Nabila; Anggita, Sahira; Nurazizah, Dina; Novitasari, Aliffiah; Nizar P, Ajeng; H, Yunita Sri; Annur M, Ade Isna; Yahya, Muhammad Ilham; Anugerah, Dandi; Nurul Istiqomah, Insya Siti; Nuryuniarti, Rissa; Saputra, Jumadil; Pratiwi, Anggia Suci; Hendrawan, Budi; Mujiarto, Mujiarto (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Covid-19 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The virus was first discovered in Wuhan, China in late December 2019. Because the virus spreads so quickly through droplets released by infected humans, the WHO (World Health Organizer) later announced that the disease is becoming an emergency requiring infected countries to impose a lock down system to slow the spread of the virus. The COVID-19 virus was first identified in Indonesia in March 2020 and the government imposed restrictions on activity and made recommendations for health protocols to be adhered to to date to prevent spread. One of the health protocols that must be adhered to is to wash your hands 6 steps properly. Hand washing can be done with soap and clean running water, or by using a hand sanitizer. The use of hand sanitizer is easy and practical because it can be taken anywhere and does not take a long time, but its availability is limited and the price is fairly expensive. Therefore, we want to teach children and teaching staff at Miftahul Khoeriyah how to make hand sanitizer independently with the basic ingredients of aloe vera, alcohol, and essential oil. This activity was carried out on September 5, 2021 located in Madrasah Miftahul Khoeriyah Bungursari Subdistrict.